Effect of Bortezomib on Total Cholesterol, Triglycerides and Histopathology Abdominal Aorta in Rats of Atherosclerosis Model - Ismawati, Ismawati; Romus, Ilhami; Maryanti, Esy; Permatasari, Nopi; Luthfianty, Elfiah (Fakultas Kedokteran Universitas Brawijaya, 2020)
The effects of using proteasome inhibitors on atherosclerosis could be beneficial or detrimental. This study aimed to analyze the effects of proteasome inhibitors in the progression stage. Experimental animals (18 rats) were divided into three groups, namely control (C) as a group of rats given standard feed, P1 as atherosclerosis-induced rat group, and P2 as atherosclerosis-induced rat group and given proteasome inhibitors. Proteasome inhibitor administered was bortezomib at a dose of 50µg/kgBW/day intraperitoneally on day 1 and 3. After four days of treatment, the termination and measurement of serum total cholesterol, serum triglycerides, and abdominal aorta histopathology with hematoxylin-eosin staining were carried out. Serum total cholesterol levels were measured using the CHOD-PAP (Cholesterol Oxidase-Peroxidase Aminoantypirin) method, whereas serum triglyceride levels were measured using the GPO-PAP (glycerol phosphatase oxidase−phenol4-amino antipyrene peroxidase) method. Histopathological assessment was carried out with a scoring system in 9 fields of view with a 400x magnification, which was then averaged. The ANOVA test showed significant differences in serum total cholesterol, serum triglycerides, and abdominal aortic histopathology between atherosclerosis and control groups, but there were no significant differences in the administration of bortezomib in atherosclerosis except in serum triglyceride levels. It can be concluded that the administration of 50µg/kg bortezomib for four days in the rats model of the progression stage of atherosclerosis can decrease serum triglyceride levels, although it can not inhibit the formation of atherosclerotic lesions and has no effect on serum total cholesterol.